Evaluation of heat capacity of CdSe quantum dots using DFT calculations - Amirul Edham, Roslee (2017)
Quantum confinement is a phenomenon that occurs upon successful control of size reduction of a semiconducting material below its exciton Bohr radius, which evolved to become quantum confined structures (QCSs), which are molecular-like, showing discrete energy transitions. These structures have been widely explored for many applications as their physical (i.e., optical and electronic) properties are deviated substantially from those of bulk materials. This study attempted to evaluate thermophysical properties of QCSs, which specified in two research objectives; (i) to calculate the heat capacity of cadmium selenide (CdSe) quantum dots (QDs) using density functional theory (DFT), and (ii) to correlate the effect of size reduction of CdSe QDs with heat capacity and Debye temperature. Structure optimisation of CdSe QD clusters were performed using DFT calculations at the Becke’s three parameters with Lee-Yang-Parr generalised-gradient approximation corrected correlation (B3LYP) hybrid functional, together with Los Alamos effective core potential plus double-ζ quality (LanL2DZ) basis sets by Gaussian 09W program package. The optimised CdSe QD clusters were analysed by thermochemical calculations of 32 different temperatures from 5 to 400 K to determine thermophysical properties of CdSe QD clusters as a function of temperature. The results of thermochemical calculations of the optimised CdSe QD clusters comprised of (i) total electronic energies, (ii) zero-point energies, (iii) molar entropies, (iv) molar thermal energies, (v) molar constant-volume heat capacities, (vi) thermal enthalpies, (vii) thermal Gibbs free energies, and (viii) numbers of vibrational mode. Evaluation of heat capacities of CdSe QD clusters showed that the QDs do not exactly follow the Debye T3 model of heat capacity. In this work, from the phonon density of states it was proven that the dispersion relation follows a square root variation for QDs, which otherwise was a constant (speed of sound) according to the Debye T3 model, and subsequently the heat capacity of the QDs were shown to follow T3/2. The thermochemically-calculated heat capacity fit very well (> 99 %) to the T3/2 model.